Changes of T cell subsets across treatments associated with prognosis in newly diagnosed follicular lymphoma - Qiuhui Jiang; Feng Lin; Zhifeng Li; Hongpeng Duan; Chong Jiang; Xingxing Yu; Caiyan Wang; Li Zhang; Xiuhua Sun; Jie Zha; Long Liu; Zhijuan Lin; et al. (Scientific Reports)
Abstract Follicular lymphoma (FL) is an immune-responsive tumor with spontaneous remission. T cells play a pivotal role in the anti-lymphoma immune response. However, the dynamics of T cells during treatment, their impact on FL clinical outcomes, and the risk factors contributing to T-cell cytopenia remain largely unexplored. T-cell and their subsets in the peripheral blood of FL patients at diagnosis, during 2–4 cycles and after 6 cycles of treatment, as well as healthy individuals were detected by flow-cytometry. The predictive effects of T cells for early progression and risks for T-cell cytopenia were analyzed. FL patients exhibited a significant decrease in CD3+, CD4+, and CD8 + T cells compared to healthy individuals, with aging intensifying the decline of CD3+, and CD4 + T cells. Notably, a reduction in CD4 + T cells, predominantly contributing to treatment-related T-cell reduction, was only observed in patients undergoing Bendamustine-based regimens. Moreover, a significantly decreased CD4 + and CD8 + T-cell at diagnosis rather than after induction therapy was observed in patients with treatment failure. Furthermore, lower CD4 + T-cell (< 260/uL) at baseline was independently correlated to early progression within 24 months. Finally, disease stage and albumin were the independent predictive factors for the decline of CD4 + T cells in FL patients. Overall, FL patients demonstrated compromised T-cell immunity, with a lower CD4 + T cell count at diagnosis correlating with treatment response and early progression. Therefore, monitoring CD4 + T cells at diagnosis might reflect immune status and aid in stratifying FL patients.